2021
DOI: 10.3390/su132313480
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Biorefinery of Microalgae (Chlorella sp.) for Producing Biofuels and Other Byproducts: A Review

Abstract: Microalgae-based carbon dioxide (CO2) biofixation and biorefinery are the most efficient methods of biological CO2 reduction and reutilization. The diversification and high-value byproducts of microalgal biomass, known as microalgae-based biorefinery, are considered the most promising platforms for the sustainable development of energy and the environment, in addition to the improvement and integration of microalgal cultivation, scale-up, harvest, and extraction technologies. In this review, the factors influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 213 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…The development of systems based on adaptive control algorithms is required because to the increasing quality control requirements for the chlorella cultivation process [7,8]. The following issues are resolved by the suggested method for implementing a set of control algorithms in the chlorella cultivation process:…”
Section: Methodsmentioning
confidence: 99%
“…The development of systems based on adaptive control algorithms is required because to the increasing quality control requirements for the chlorella cultivation process [7,8]. The following issues are resolved by the suggested method for implementing a set of control algorithms in the chlorella cultivation process:…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated that lutein can resist the damage of blue-light irradiation [34,75,76]. The raw materials of the lutein used are mainly extracted from plants [77,78] or produced in synthetic media by microorganisms [79,80] and microalgae [6,81]. In this study, the lutein produced by a biomass of Chlorella sp.…”
Section: Damage Of Nih/3t3 Cells From Blue-light Irradiationmentioning
confidence: 97%
“…Firstly, the NIH/3T3 cells were irradiated with blue light for different exposure times to investigate the relationship between the ROS content in the cells and the cell viability resulting from blue-light irradiation. The cell viability effect of blue light under different exposure times (3,6,12,18, and 24 h) on NIH/3T3 cells is shown in Figure 5. Lower viability of NIH/3T3 cells concurred with a longer period of blue-light irradiation.…”
Section: Damage Of Nih/3t3 Cells From Blue-light Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several real-world examples highlight the success of Chlorella-based dairy wastewater treatment and livestock feed production [28][29][30][31]. By reducing nutrient pollution, providing highquality nutrition for livestock, and contributing to the circular economy, this approach aligns with the principles of sustainable agriculture and resource conservation [32].…”
Section: Introductionmentioning
confidence: 99%